Molecular basis of permethrin and DDT resistance in an Anopheles funestus population from Benin - Tchigossou, Genevieve M; DJOUAKA, Rousseau; Akoton, Romaric; Riveron, Jacob; Irving, Helen; Atoyebi, Seun M; MOUTAIROU, KABIROU; YESSOUFOU, AKADIRI; Wondji, S. Charles (My University, 2018)
Background: Insecticide resistance in Anopheles mosquitoes is threatening the success of malaria control programmes. In order to implement suitable insecticide resistance management strategies, it is necessary to understand the underlying mechanisms involved. To achieve this, the molecular basis of permethrin and DDT resistance in the principal malaria vector, Anopheles funestus from inland Benin (Kpome), was investigated. Results: Here, using a microarray-based genome-wide transcription and qRT-PCR analysis, we showed that metabolic resistance mechanisms through over-expression of cytochrome P450 and glutathione S-transferase genes (GSTs) are a major contributor to DDT and permethrin resistance in Anopheles funestus from Kpome. The GSTe2 gene was the most upregulated detoxification gene in both DDT- [fold-change (FC: 16.0)] and permethrin-resistant (FC: 18.1) mosquitoes suggesting that upregulation of this gene could contribute to DDT resistance and cross-resistance to permethrin. CYP6P9a and CYP6P9b genes that have been previously associated with pyrethroid resistance were also significantly overexpressed with FC 5.4 and 4.8, respectively, in a permethrin resistant population. Noticeably, the GSTs, GSTd1-5 and GSTd3, were more upregulated in DDT-resistant than in permethrin-resistant Anopheles funestus suggesting these genes are more implicated in DDT resistance. The absence of the L1014F or L1014S kdr mutations in the voltage-gated sodium channel gene coupled with the lack of directional selection at the gene further supported that knockdown resistance plays little role in this resistance. Conclusions: The major role played by metabolic resistance to pyrethroids in this An. funestus population in Benin suggests that using novel control tools combining the P450 synergist piperonyl butoxide (PBO), such as PBO-based bednets, could help manage the growing pyrethroid resistance in this malaria vector in Benin.
Keywords: Anopheles funestus; DDT; Insecticide resistance; Kpome; Permethrin; Resistance mechanisms